Covid-19, Mortality and Inequality in Sarawak - Juna, Liau; Sharifah Sophia, Wan Ahmad; Siti Zanariah, Ahmad Ishak (UNIMAS Publisher, 2023)
The first two males’ mortality in Malaysia due to COVID-19 announced by the authority on March 13, 2020. The fatalities became the major headlines on the media. Although many people discussed ‘actively’ about COVID-19, however conversations about deaths or funerals of victims from COVID- 19 are quite ‘passive’ during the initial stage of the pandemic. When death occurs, biomedical examiners must examine death causation, mechanism and manners of death because COVID-19-related deaths are contagious. As a results, corpses are managed by authorised personnel with no or limited intervention from family or community members. These social responses to deaths from COVID-19 are paradox as funerals are traditionally communities’ responsibility. Due to surging cases of COVID-19, drastic measures are taken by the government globally to prevent the spread of COVID-19 and for social, economy and environment sustainability. This study aims to examine COVID-19 mortality patterns and its socio-cultural dimensions in Sarawak. Data are collected in the duration of 18 months from official sources and from participant observation. Data are analysed in several aspects including age, gender and co-morbidity. The findings show that mortality rates among males are significant higher compared to females. Most casualties occurred among age groups: 70-79, 60-69 and 50-59. The majority of cases have co-morbidity.